International Language Literacy: Technical Assistance in Proofreading Scientific Articles for Publication in Accredited Journals - N. Hula, Ibnu Rawandhy; Mariana, Ana; Paputungan, Moh. Zulkifli; Petta Solong, Najamuddin (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2024)
This study aims to explore and analyse the process of technical assistance in proofreading scientific articles and measure its impact on the quality of writing and chances of publication in accredited journals. Technical assistance consists of six stages: (1) Needs Identification, (2) Training, (3) Individual Mentoring, (4) Use of Assistance Tools, (5) Evaluation and Feedback, and (6) Application of Results & Submit Articles. This research uses mixed methods, with data collection through questionnaires and documentation. The study population was 20 students, all of whom were sampled using a purposive sampling technique. The mentoring process involved 2 experts and 3 proofreaders. The results showed that this service activity produced 20 articles that were eligible for submission, with an initial score of 420 (70.00%) increasing to 478 (79.67%) at 78.33%. The articles have been written according to the template, corrected, translated, checked for plagiarism, and submitted to Sinta accredited national journals, with details: 1 article to S-5 journal, 14 articles to S-4 journal, 1 article to S-3 journal, 2 articles to S-2 journal, and 2 articles to international proceedings. This research shows that technical assistance is effective in improving the quality of scientific articles and publication opportunities in accredited journals. The findings can serve as a reference for educational and research institutions in developing similar programmes to increase the productivity of scientific publications.